Work process of nursing team in alcoholism treatment program - Comper, Emilly; Queiroz Subrinho, Lucas; Batista Portugal, Flávia; Mechelli de Siqueira, Marluce (Guará Journal, 2022)
Alcoholism produces changes in individual and collective heal-th, resulting in very important physical, psychic, and social ma-nifestations, requiring a full and networked intervention. The aim of this study is to describe the work process of the nursing team in the Program of Attention to the Alcoholic Patients (PAA) of the University Hospital Cassiano Antônio Moraes (HUCAM) of the Federal University of Espírito Santo (UFES). The technique of general direct observation (professionals) and specific (nursing team) and documentary research (reports, articles, and books) was used to capture the reality of the Program’s assistance. PAA-HUCAM-UFES is an outpatient service for the treatment of alcoholism patients, with an interprofessional approach com-posed of Nurse, Doctor and Social Worker. The health professio-nals attend in program on Mondays, Wednesdays, and Thurs-days. The nursing team develops the Nursing Consultation (CE) with health education activities to supply the Basic Human Ne-eds (NHB) and to promote the self-care of the alcoholic patient, based on Wanda Horta and Orem Theory. Through more than 30 years of experience, the nursing team has been developing the care of the alcoholic, seeking their autonomy, their active role and respect for their human rights.